The Family Hope Program: An effort in Poverty Alleviation in Kepil District, Wonosobo Regency - NUGRAHA, Irwan Abdu; NUGRAHAENI, Fitria Marlina (Integration: Journal Of Social Sciences And Culture, 2023)
Purpose:This research examines the process during the implementation of the Family Hope Program in Kepil District, Wonosobo Regency. The research used a qualitative descriptive method, using primary and secondary data as data sources. Methodology: The researcher conducted in-depth interviews with stakeholders supported by literature sources from journals, books, and the internet to obtain primary data. Four indicators were used to see the Family Hope Program policy implementation: Communication, Resources, Bureaucratic Structure, and Disposition. Findings: The results of this study show that communication is done hierarchically between the central government and the local government, which can then be socialized with Family Hope Program recipient communities Implication:In addition, the resources appointed to carry out this Socialization must meet the requirements and be trained to socialize the program well with the community. However, Family Hope Program recipients must still be targeted in the field.